Detection of Helicobacter pylori in oropharyngeal lymphatic tissue with real-time PCR and assessment of its carcinogenic potential - Lukeš, Petr; Pavlík, Emil; Potužníková, Běla; Nártová, Eva; Lukešová, Eva; Plzák, Jan; Katra, Rami; Šterzl, Ivan; Bartůňková, Jiřina; Betka, Jan; Astl, Jaromír (European archives of oto-rhino-laryngology, 2014)
Helicobacter pylori (HP) is considered a major gastric pathogen with oncogenic potential. The aim of this study was to determine whether HP is present in oropharyngeal lymphoid tissue and whether oropharyngeal HP strains carry virulence factor genes known to be involved in gastric carcinogenesis. The study included 104 subjects (41 patients with tonsillar carcinoma, 38 with chronic tonsillitis and 25 with obstructive sleep apnoea syndrome--OSAS). Detection of specific serum anti-HP antibodies was performed with an ELISA. The presence of HP in tissue was determined by culture and real-time PCR. Detection of virulence factors genes was also performed. Specific antibodies were found in 78.05% of tumour cases, 34.21% of chronic tonsillitis cases, and 72.0% of OSAS cases. The presence of HP in the tissue was detected in 73.91% of tonsillar tumours, 70.0% of tonsillitis cases, and 69.23% of OSAS specimens. The results of the virulence factor gene analysis showed the majority of the s1b (52.4%) and m2 (59.5%) alleles of vacA gene and limited abundance of cagA gene (12.5%). Results confirm that HP may colonise oropharyngeal lymphoid tissue. Oropharyngeal HP colonisation was frequently found in the oropharyngeal cancer group and in patients with benign oropharyngeal diseases. A virulence factor gene analysis showed differences from the predominant strains most commonly found in the stomach. The strains obtained from the oropharynx differed primarily by the lower abundance of the cagA gene and carried the less virulent vacA gene allele combination.
Keywords: Oropharynx; infekce vyvolané Helicobacter pylori; Helicobacter pylori; lymfoidní tkáň; chronická nemoc; Bacterial Typing Techniques; Antibodies, Bacterial; Humans; tonzilární nádory; lidé; tonzilektomie; Chronic Disease; kvantitativní polymerázová řetězová reakce; ELISA; faktory virulence; Sleep Apnea, Obstructive; bakteriální proteiny; Helicobacter Infections; Real-Time Polymerase Chain Reaction; Bacterial Proteins; Carcinoma, Squamous Cell; orofarynx; antigeny bakteriální; Enzyme-Linked Immunosorbent Assay; protilátky bakteriální; Antigens, Bacterial; Head and Neck Neoplasms; tonzilitida; Lymphoid Tissue; Tonsillitis; techniky typizace bakterií; spinocelulární karcinom; nádory hlavy a krku; Virulence Factors; Tonsillectomy; obstrukční spánková apnoe; Tonsillar Neoplasms